Philosophy and literature in the interwar period: philosophical anthropology of M. Unamuno and H. Hesse - Teytelbaum, Elena (Opción, 2019)
The impact of the First World War and the spiritual crisis of interwar Europe on the works of M. Unamuno and H. Hesse is examined in this article. The particularity of considering the problem of war in the works of M. Unamuno and H. Hesse is analyzed taking into account the country of origin of the authors: Hesse was a citizen of a belligerent country, while Unamuno was a citizen of a country, which officially remained neutral. Moreover, the article explores the features of existence of philosophical reflection in artistic space, as well as the relationship of philosophy and literature in the works of M. Unamuno and H. Hesse – the relationship, within which literature is viewed as a laboratory for philosophical ideas. In addition, the article analyzes the problem of personality's multiplicity, struggle and agony in the philosophical anthropology of the above- mentioned authors in its connection with the spiritual crisis of the early 20th century.